Mudanças globais e o futuro das plantas carnívoras: riscos iminentes e estratégias de conservação de Drosera. - Julio Cesar Santiago Lopes (2022)
The biodiversity loss has increased considerably in recent decades and carnivorous plants are among the most threatened organisms. Inhabiting seasonally flooded and nutrient-poor environments, Drosera represents the most endangered carnivorous plant genus in South America. Among the main causes rising the decline of several Drosera populations are global changes with drastic reductions in rainfall and prolonged dry periods, increased nitrogen deposition, as well as the destruction of their habitats mainly for agricultural use. Most South American Drosera species are endemic and spatially restricted, reinforcing the need to assess the degree of habitats vulnerability and the urgency of developing conservation strategies in the face of global changes. Here, we developed species distribution models (SDM's) in order to obtain a comprehensive overview of Drosera's distribution, establish the main risks to the habitats occupied by these species, and identify priority areas for the conservation of the genus in South America. The greatest richness, diversity and endemism of Drosera is found especially in campo rupestre, a mountainous ecosystem extremely threatened by human activities such as agriculture and mining. Particularly, these are the main activities responsible for the destruction of Drosera habitats worldwide. Our results exhibit a catastrophic future scenario with loss of approximately 90% of the area of environmental suitability for Drosera survival in South America by 2050 and 2070. The impacts of a possible extinction of Drosera species extend beyond their biological diversity, as well as the numerous ecological processes and ecosystem services with which they are associated. The prospect for sundew species in South America shows us a pessimistic scenario, its habitat is under constant human activity pression and the risk to many species extinction in the near future is crucial. The creation and maintenance of protected areas and conservation units may be an effective strategy in the short term; however, it is necessary to devise new strategies for Drosera conservation in South America that guarantee its long-term survival in the face of global climate change.